The European Debt Crisis : Has the EMU membership been a gift or a curse? - Guerrisi, Meryem Su Esmahan (2023)
The purpose of the thesis is to assess the impact of the European Economic and Monetary Union (EMU) membership in Portugal, Ireland, Italy, Greece and Spain during the European Debt Crisis. This will be accomplished by a comparison of those five eurozone nations’ performance with that of Bulgaria, Estonia, Latvia and Lithuania, who were not members of the EMU throughout the crisis. Furthermore, this thesis focuses on the evaluation of the financial accounts and Target 2 Balances of the countries. The study uses a mixed-methods approach, including a comprehensive literature review of relevant sources and a case study based on publicly available data to analyze the economic performance of the mentioned countries. The findings of the study indicate that both groups of countries encountered significant challenges during the European Debt Crisis in 2008. However, the non-eurozone members were able to weather those challenges faster and more successfully in the long-term. These findings are further supported by the literature review, which highlights the delayed response to the crisis within the EMU and raises concerns about the effectiveness of the union’s initiatives.